2017
DOI: 10.1016/j.ijrobp.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Androgen Deprivation in Locally Advanced Prostate Cancer: Long-Term Update of NRG Oncology RTOG 9202

Abstract: Purpose Trial**** was a phase III randomized trial designed to determine the optimal duration of androgen deprivation therapy (ADT) when combined with definitive radiation therapy (RT) in the treatment of locally advanced non-metastatic adenocarcinoma of the prostate. Long-term follow-up results of this study now available are relevant to the management of this disease. Materials and Methods Men (N=1,554) with adenocarcinoma of the prostate (cT2c-T4, N0- Nx) with a prostate specific antigen (PSA) <150ng/ml a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 110 publications
(54 citation statements)
references
References 20 publications
1
51
0
2
Order By: Relevance
“…Equally critical in the evaluation of the pattern of use of ADT is the timing and duration of ADT. For men with high-risk PCa, multiple randomized controlled trials, including RTOG 92-02, EORTC 22961 and TROG 03.04, have all shown that short-term ADT (3-6 months) is inferior to long-term ADT (1.5-3 years) [6,7,9,33], and for men with intermediate-risk PCa, there are some data suggesting that 6-8 months of ADT is superior to 3 months of ADT [3,8]; however, there is little evidence as to whether longer-term ADT in men with intermediate-risk PCa provides further clinical benefits. Unfortunately, given the nature of data captured in PCOR-Vic, there are no data on duration or type of ADT used for each patient, which is another limitation of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Equally critical in the evaluation of the pattern of use of ADT is the timing and duration of ADT. For men with high-risk PCa, multiple randomized controlled trials, including RTOG 92-02, EORTC 22961 and TROG 03.04, have all shown that short-term ADT (3-6 months) is inferior to long-term ADT (1.5-3 years) [6,7,9,33], and for men with intermediate-risk PCa, there are some data suggesting that 6-8 months of ADT is superior to 3 months of ADT [3,8]; however, there is little evidence as to whether longer-term ADT in men with intermediate-risk PCa provides further clinical benefits. Unfortunately, given the nature of data captured in PCOR-Vic, there are no data on duration or type of ADT used for each patient, which is another limitation of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple randomized controlled trials to date have consistently shown that adding ADT to RT is associated with improved overall survival in men with intermediate-to high-risk PCa [1][2][3][4][5]; however, controversies remain regarding the role of ADT given the potential side effects, deterring some radiation oncologists from prescribing ADT with RT. There are also ongoing controversies regarding timing, duration [6][7][8][9] and type of ADT prescribed [10][11][12]. Recent findings from the US National Cancer Database (NCDB) have shown that, over time, there is a decreasing trend in the use of ADT with RT in men with intermediate-risk PCa [13].…”
Section: Introductionmentioning
confidence: 99%
“…Several randomized trials and meta-analyses performed in the 1990s and 2000s showed a significant benefit of androgen deprivation therapy (ADT) combined with RT in terms of biochemical control and overall survival (OS) among patients with intermediate-risk and high-risk PC [4][5][6][7]. Because the relatively low irradiation doses (65-70 Gy) were used in those trials, the optimal duration of ADT to use in combination with high-dose RT remains unknown [8].…”
Section: Introductionmentioning
confidence: 99%
“…In all studies, there was greater benefit with adjuvant ADT given for at least 3 months compared with no ADT, and the panel concluded that optimal dosing of ADT for use with RT is 4 to 6 months for intermediate-risk patients and 18 to 36 months for high-risk patients. [23][24][25][26][27][28][29] The first dose of ADT should be administered 1 to 2 months before beginning RT. ability to measure PSA with ultrasensitive assays advances, these definitions may change.…”
Section: The Role Of Adt As Primary Therapy For Localized Pcmentioning
confidence: 99%